Irinotecan (CPT-11) Treatment Induces Mild Gonadotoxicity - Levi, Mattan; Ben-Aharon, Irit; Shalgi, Ruth (Frontiers in Reproductive Health, 2022)
Background: Gonadal toxicity following chemotherapy is an important issue among the population of young cancer survivors. The inhibitor of DNA topoisomerase I, irinotecan (CPT-11), is widely used for several cancer types. However, little is known about the effect of irinotecan on the fertility of both genders. Thus, the aim of the present study was to evaluate irinotecan gonadotoxicity, using a mouse model. Methods Mature male and female mice were injected intraperitoneally with either saline (), irinotecan (100 mg/kg) or cyclophosphamide (100 mg/kg); and sacrificed one week or three months later for an acute or long-term toxicity assessment, respectively. We used thorough and advanced fertility assessment by already established methods: Gonadal and epididymal weights, as well as sperm count and sperm motility were determined; serum anti-Müllerian hormone (AMH) was measured by ELISA. Immunohistochemistry (Ki-67), immunofluorescence (PCNA, CD34), terminal transferase-mediated deoxyuridine 5-triphosphate nick-end labeling (TUNEL) and computerized analysis were performed to examine gonadal proliferation, apoptosis and vascularization. qPCR was used to assess the amount of testicular spermatogonia (Id4 and Gafra1 mRNA) and ovarian primordial oocytes reserves (Sohlh2, Nobox and Figla mRNA). Results Females: Irinotecan administration induced acute ovarian apoptosis and decreased vascularity, as well as a mild, statistically significant, long-term decrease in the number of growing follicles, ovarian weight, and ovarian reserve. Males: Irinotecan administration caused an acute testicular apoptosis and reduced testicular spermatogenesis, but had no effect on vascularity. Irinotecan induced long-term decrease of testicular weight, sperm count and testicular spermatogonia and caused elevated serum AMH. Conclusion Our findings imply a mild, though irreversible effect of irinotecan on mice gonads.